Integrated Treatment Approach in Hemiplegic Stroke Patient: A Case Study (International Journal of Ayurveda and Pharma Research, 2022)
Hemiplegic stroke is one of the major prevalent mortality in many countries including India. In hemiplegic stroke spasticity, and muscle atrophy results in the inability to move certain muscles. Most post-stroke complications like inability and shoulder pain are a major concern for therapeutic interventions. Recent advances have been made in the interdisciplinary approach of rehabilitation, artificial intelligence, brain-computer interface, and much more mainly targeting post-stroke complications. In the present case report study 55-year-old male addicted to tobacco, altered HBA1c, elevated neutrophils, erythrocyte sedimentation rate, and C-reactive protein and CT scan report of mild cerebral atrophy suggestive of hemiplegic stroke. The patient was admitted on a stretcher with no sensation in his left hand and Vaksanga (impaired speech). After receiving the patient and family member's consent the integrated treatment was initiated. After 15 days of integrated treatment including T-AYU-HM Premium, significant improvement in the patient’s condition was noticed. The patient recovered from the impaired mobility of the left hand and remarkable improvement in slurred speech. This confirms that the intervention of Ayurvedic medicine in post-stroke management and prevention of stroke might play a crucial role. More such kinds of interventional case studies or trials should be warranted to justify the same.